FREQUENCY AND PATTERN OF BONE MARROW INVOLVEMENT AMONG PATIENTS WITH NON HODGKIN LYMPHOMA - Zahur, Umar; Zafar, Lubna; Khaliq, Sehar; Rehan, Madeeha; Khalid, Attika (Journal of Ayub Medical College Abbottabad, 2014)
Background: Non-Hodgkin lymphoma (NHLs) are a heterogeneous group of lymphoid neoplasms, characterized by an irregular pattern of spread and may present with extranodal involvement This study was conducted to determine the frequency and pattern of Bone marrow involvement on trephine biopsy in cases of Non-Hodgkin lymphoma (NHL). Methods: This cross sectional study was conducted in Pathology department of Fauji Foundation Hospital (FFH)/Foundation University medical college (FUMC) Rawalpindi, from14th December 2010 to 14th December 2011. One hundred and six patients with histopathologically confirmed Non-Hodgkin lymphoma on lymph node (LN) biopsy, who had not received any chemotherapy were selected and Bone Marrow (BM) trephine biopsies for staging were performed on them. Results: Out of one hundred and six patients, forty five (42.5%) were diagnosed to have Bone Marrow involvement on staging. The most common pattern was diffuse, i.e., 44.44%, followed by the interstitial infiltrate in 28.89%, focal and mixed constituted 11.11% each, and paratrabecular pattern was found in 4.44%. Conclusion: This study highlights the high incidence of involvement and diffuse pattern in the Bone marrow biopsies of newly diagnosed Non-Hodgkin lymphoma, both of which indicate poor prognosis. Keywords: Non-Hodgkin lymphoma; bone marrow; prognosis; staging